Changes in echocardiographic parameters in iron deficiency patients with heart failure and chronic kidney disease treated with intravenous iron - Toblli, Jorge Eduardo (2015)
BACKGROUND: Treatment of iron deficiency helps to improve cardiac and renal function in patients with chronic heart failure. However, the mechanism by which this occurs is currently unclear. METHODS: We undertook a double-blind, randomised, placebo-controlled study of intravenous iron sucrose treatment (200mg/mL weekly for five weeks) in patients with chronic heart failure, chronic kidney disease and iron-deficiency anaemia receiving optimal treatment for chronic heart failure (N=60). Markers of disease severity, iron status, anaemia and inflammation were measured during a six-month follow-up period, and evaluation of echocardiographic parameters was performed at baseline and six months after treatment. RESULTS: At six months after treatment initiation, intravenous iron was associated with reduced severity of the symptoms of chronic heart failure and improved renal function (both p<0.001 versus control). Also, ferritin and transferrin saturation levels were increased, as were haemoglobin levels, whereas inflammatory markers were reduced (all p<0.001 versus control). Left ventricular systolic and diastolic diameters were increased and improved left ventricular function correlated with iron status in patients receiving intravenous iron but not patients in the control group. CONCLUSIONS: Intravenous iron treatment was associated with improved myocardial functional parameters and cardiac dimensions in patients with anaemia and chronic kidney disease.